Pelatihan Penulisan dan Publikasi Artikel Penelitian Tindakan Kelas di Jurnal bagi Cendekiawan Pendidikan - Imam Rofiki; Dwi Setiawati Radjak; Mudjia Rahardjo; Winarno (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
Understanding and having the skills for conducting Classroom Action Research (CAR) or Penelitian Tindakan Kelas (PTK) for educators and prospective educators are still inadequate, due to lack of knowledge in writing and publishing in national journals. This service aims to provide training in writing and publishing PTK articles in national and international journals for educational scholars. Service activities are carried out in the form of online training, involving 78 educational scholars throughout Indonesia, in a national seminar initiated by the Research Training Institute "Malang Research Training Center'' (LPP-MRTC). The method used in carrying out the activities is webinars via Zoom meeting, which consist of material presentation, question and answer, and discussion, as well as training assistance through WhatsApp Group. This activity was carried out in two stages, namely the preparation stage and the implementation stage. The research results showed that 57% of participants said they were very enthusiastic, 39% of participants said they were enthusiastic, and 4% of participants said they were neutral. Therefore, through this training, participants obtained additional insight and understanding into writing and publishing PTK results in journals.